RC hollow-pier modelling and shear influence on the cyclic numerical response - António Arêde (2009)
Non-linear reinforced concrete bridge piers' cyclic behavior is known for being influenced by shear. That is particularly visible in the case of hollow piers where the deformation and collapse mechanisms are frequently shear-based. Since the design codes are still relatively conservative regarding the evaluation of those effects, this work intends to presentthe influence that shear has on the numerical response of hollow piers, as well as providing abasis for the discussion of adequate modeling strategies.The studies related to this work were based on several finite element models, wherein concretewas represented by 3D elements while steel reinforcement was represented by linearbar elements. Concrete non-linear behavior was simulated according to a damage model that determines the stress state in the principal directions space, resorting to two independent scalar damage variables representing the compressive or tensile accumulated damage. Steel reinforcement was simulated according to the features of the Menegotto-Pinto model. The aforementioned models were calibrated with the experimental data taken from the testsmade at LESE (Laboratory of Earthquake and Structural Engineering) from FEUP (Faculty of Engineering of University of Porto) on reduced scale (1:4) physical models. The numerical analyses were made with the structural analysis software CAST3M.